Incidence of in‐hospital and post‐discharge diagnosed hospital‐associated venous thromboembolism using linked administrative data. Issue 2 (7th February 2018) - Stubbs, Joanne M.; Assareh, Hassan; Curnow, Jennifer; Hitos, Kerry; Achat, Helen M.
Abstract: Background: Hospital‐associated venous thromboembolism (HA‐VTE) is a serious adverse event, preventable with appropriate care during and post‐admission. Accurate measurement of in‐hospital and post‐discharge incidences is essential for implementation and evaluation of prevention strategies and monitoring. Aims: To estimate in‐hospital and post‐discharge diagnosed VTE, trends and risk factors. Methods: This was a population‐based study in New South Wales, Australia, using linked hospital admission and emergency department data for 2010–2013 of adult patients with a minimum stay of 48 h. HA‐VTE were diagnosed in‐hospital or post‐discharge (within 90 days). Multi‐level modelling schemes produced adjusted rates and ratios for patient, admission and hospital‐related characteristics. Results: From 1 865 059 admissions, the HA‐VTE incidence rate was 9.7 per 1000 admissions; 71% were diagnosed post‐discharge, and 4.3% died with a greater risk for VTE diagnosed in hospital compared to post‐discharge (8.4% vs 2.6%, P < 0.001). Compared with surgical patients, medical patients developed fewer HA‐VTE (IRR = 0.60, 95% CI: 0.58–0.63) but were more likely to be diagnosed post‐discharge (OR = 2.19; 95% CI: 2.00–2.40). HA‐VTE increased 6.5% over the period, driven by the 44% increase in in‐hospital diagnoses and not by the 9% decrease in post‐discharge diagnoses. Conclusions: HA‐VTE is a continuing burden, and diagnosis after recent hospital discharge is notably high. Incidence varies across patients and facilities, highlighting the need for individual VTE risk assessment. Inclusive measures and routine monitoring of HA‐VTE incidence and mortality are essential for implementing best practice and assessing effectiveness of prevention strategies.